ANTIBACTERIAL ACTIVITY TEST OF FENNEL LEAVES AND STEMS (Foeniculum vulgare Mill.) AGAINST BACTERIA Cutibacterium acnes AND Staphylococcus epidermidis - Ni Luh Putu Kris Monika Yanti; Madahlena Isaura Dasilva; Putu Ririn Andreani; I Kadek Suardiana (Journal Pharmaceutical Science and Application, 2025)
Background: Acne vulgaris is a common skin problem that often affects adolescents and young adults, caused by the bacteria Cutibacterium acnes and Staphylococcus epidermidis. The use of synthetic antibiotics for acne treatment can lead to resistance; therefore, it is necessary to develop alternative natural ingredients that can act as a companion or complementary therapy, such as fennel plants (Foeniculum vulgare Mill.). Objective: To identify and compare the antibacterial activity of ethanol extracts of fennel leaves and stems against C.acnes and S.epidermidis. Methods: Extraction is carried out by maceration using 96% ethanol. Antibacterial tests were carried out in vitro using disc diffusion methods with concentrations of 50%, 75%, and 100%. Tetracycline 1% is used as a positive control, and DMSO 10% as a negative control. Results: Extracts of fennel leaves and stems exhibited antibacterial activity. The diameter of the inhibition zone increased with increasing extract concentration, with the leaves extract showing greater antibacterial activity than the stems extract. Conclusion: The results of the antibacterial activity test showed that ethanol extracts of leaves and fennel stems were able to inhibit the growth of C. acnes and S. epidermidis, with an average inhibition zone of leaf extract that was more optimal than that of stems.